Show that for non-zero natural numbers k and n. \(\left \{k,n \right \}\subset\left \{ \mathbb{N}\setminus \left \{ 0 \right \} \right \}\)

\(k\cdot (k+1)\cdot (k+2)\cdot (k+3)\cdot ...\cdot(k+n-1)\) is divisible by \(n!\)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet \(c\equiv k (mod\quad { n })\) with \(0\le c<n\) then \(k+n-c\) is a factor in the product. Since \(c\equiv k(mod\quad { n })\), then \((k+n-c)(mod\quad n)\equiv (k-c) (mod\quad n)\equiv 0\) and since one of the factors is divisible by \(n\) the product must be as well

Log in to reply

\(k+n-c\) is factor if \(k\) is not a factor.

\(1\leq c <n\)

If \(k\) is divisible by \(n\) then there is nothing left to prove.

Edit: Also, \(k+n-c \leq k+n-1\)

\(-c \leq -1\)

\(c \geq 1\)

Log in to reply